Edukasi kepada Ibu Hamil tentang Selfhypno Pregnancy Distraksi Musik Instrumentalia Melayu Jambi dalam Mengatasi Ketidaknyamanan Kehamilan Trisemester III - Gustina Gustina; Arifarahmi Arifarahmi (Universitas Baiturrahim, 2026)
Discomfort during pregnancy, especially the third trimester such as back pain, shortness of breath, frequent urination, difficulty sleeping, cramps, odem, varicose veins, heartburn, constipation, constipation, fatigue and fatigue. This situation really requires proper handling by obstetric practitioners, prenatal care for mothers is expected to help in overcoming discomfort during pregnancy, especially this third trimester pregnancy. The most common III trimester discomfort is back and back pain. Pharmacologically, pain can be treated with analgesic therapy which is the most commonly used method for pain relief. Non-pharmacologically, pain can be treated, one of which is with distraction techniques. The most effective distraction technique to reduce pain is listening to classical music (mozart) and also back exercises. Another non-pharmacological treatment is hypnotherapy, which is a method of implanting suggestions when the brain is in a relaxed state, but that does not mean falling asleep or not being self-conscious during practice. This method of service is to provide education to see the knowledge of trisemster III pregnant women about selfhypnopregnancy distraction with Jambi Malay instrumental music in overcoming the discomfort of trimester III pregnancy, then pre and post education evaluations are carried out. The results of the activity were: from 15 trimester III pregnant women who participated in pre-education activities 15 people, Good knowledge of 4 (26,66) people and 11 (73,33%) people of poor maternal knowledge about selfhypnopregnancy distraction with Jambi Malay instrumental music in overcoming the discomfort of pregnancy in the third trimester and after education from 15 pregnant women trimester III Good knowledge of 14 (93,33%) people and poor knowledge of 1 (6,66%) people. Conclusion there was an increase in pre and post education monitoring in trimester III pregnant women. Suggestion, that this knowledge be given to all trimester III pregnant women so that mothers can overcome the discomfort of trimester III with selfhypnopregnancy distraction with Jambi Malay instrumental music to keep pregnant women fit during pregnancy